X^2(x+4) x 3x^2(x-1)
(X^3+4x^2) x (3x^3 -3x^2)
3x^6 -3x^5+12x^5 -12x^4
3x^6 +9x^5-12x^4
I think that’s how you do it
Answer:
34'2" I think
Step-by-step explanation:
You just add them together and that was for the first part
Answer:
75.39 in^2 (round to the nearest hundreds)
Step-by-step explanation:
I think that we have to find the lateral area
circumference = 2 x radius x pi = 2 x 4 x pi = 25,13 in^2 (round to the nearest hundreds)
lateral surface = (circumference x slant height)/2 = (25,13 x 6)/2 = 75,39 in^2 (round to the nearest hundreds)
The simplified form of the expression [5.5(x+6 1/2)-(x+9 1/3)-(19-x)] is 11x/2 + 89/12
<h3>What is the simplified form of the expression</h3>
Given the expression;
5.5(x+6 1/2) - (x+9 1/3) - (19-x)
First, we convert 6 1/2, 9 1/3 and 5.5 to an improper fraction
6 1/2 = 13/2, 9 1/3 = 28/3 and 5.5 = 11/2
So, we have
(11/2)( x + 13/2 ) - ( x + 28/3 ) - ( 19 - x )
Next, we remove the parentheses
11x/2 + 143/4 - x - 28/3 - 19 + x
11x/2 + 143/4 - 28/3 - 19
11x/2 + 317/12 - 19
11x/2 + 89/12
Therefore, the simplified form of the expression [5.5(x+6 1/2)-(x+9 1/3)-(19-x)] is 11x/2 + 89/12.
Learn more about fractions here: brainly.com/question/28039882
#SPJ1